SISTEM INFORMASI PERMINTAAN PEMBELIAN BARANG DENGAN KONTROL BUDGET BERBASIS WEB (STUDI KASUS PT AGEL LANGGENG PASURUAN) - Mochamad Muzaini; Arif Senja Fitrani,S.Kom,M.Kom (Research Parks Publishing LLC, 2020)
Work efficiency is now a top priority in every company. One form to support efficiency is by changing the old way of working to become more modern. To apply this, a program was created that could help speed up work and also minimize data errors and decision making. The system used is through a web-based program that can be accessed by all parts quickly because it is connected to the network. From the results of research conducted, it is known that using this program is able to accelerate the process of submitting goods requests. And also can quickly find out the arrival date of the goods and the budget used.